What's smart about smart specialization – a new EU innovation strategy or more of the same?. Issue 12 (4th June 2020) - Eklinder-Frick, Jens Ola; Perna, Andrea; Waluszewski, Alexandra
Abstract : Purpose: The aim of this paper is to outline what the intended benefits the smart specialization strategy (S3) is meant to create, and through what policy measures; that is, to shed light over what underpinnings S3 is based on, and if the measures based on these can affect the relations between "academia, businesses, and local authorities" – where the public and the private actors might have partly overlapping interests, but with different needs and rationales. Design/methodology/approach: The research design of this paper is based on the industrial marketing and purchasing network approach, that is, the empirical observation that business exchange has a content, which affects and gives imprints on the actors engaged in the exchange. To determine whether the S3 strategy in general, and in the two investigated regions in particular, can affect the embedding of innovations in using, producing and developing settings, and if so how, this study applied the actors–resources–activities model. In addition to investigation of the S3 strategy in general, two case studies were conducted, one each in two European Union regions with rather different business and academic research characteristics: the Marche region in Italy and the Uppsala region in Sweden. Findings: The S3 measures rest on the judgement of which "domains" to support can be made by policy actors without deeper analysis of how the assumed firms representing these domains are related in terms of how resources are combined and activated. Instead, the S3 policy analysis is based on local policy organizations desk table investigations of what appears as innovative. Hence, in practice, the key S3 measure is still to transfer knowledge from the public to the private sector. This entails that support in terms of how to create change in established resources interfaces, which is a main source of innovation to which both established and emerging localized firms are related, remains out of policy sight. Originality/value: The ambition with this paper is to discuss what changes S3 – with the ambition to develop and match academic research to business needs – implies and what underpinnings it is resting on. Hence, the focus is directed to what new types of policy arrangements are supposed to result in what types of benefits – and last but not least, the ability for these to interfere with businesses which are interconnected across spatial borders.